A high-performance cathode for the next generation of solid-oxide fuel cells - Shao, Zongping; Haile, S. (2010)
© 2011 Nature Publishing Group, a division of Macmillan Publishers Limited and published by World Scientific Publishing Co. under licence. All rights reserved.Fuel cells directly and efficiently convert chemical energy to electrical energy1. Of the various fuel cell types, solid-oxide fuel cells (SOFCs) combine the benefits of environmentally benign power generation with fuel flexibility. However, the necessity for high operating temperatures (800–1,000 °C) has resulted in high costs and materials compatibility challenges2. As a consequence, significant effort has been devoted to the development of intermediate-temperature (500–700 °C) SOFCs. A key obstacle to reduced-temperature operation of SOFCs is the poor activity of traditional cathode materials for electrochemical reduction ofoxygen in this temperature regime2. Here we present Ba0.5Sr0.5-Co0.8Fe0.2O3-d(BSCF) as a new cathode material for reducedtemperature SOFC operation. BSCF, incorporated into a thin-film doped ceria fuel cell, exhibits high power densities (1,010mWcm-2and 402mWcm-2at 600 °C and 500 °C, respectively) when operated with humidified hydrogen as the fuel and air as the cathode gas. We further demonstrate that BSCF is ideally suited to ‘single-chamber’ fuel-cell operation, where anode and cathode reactions take place within the same physical chamber3. The high power output of BSCF cathodes results from the high rate of oxygen diffusion through the material. By enabling operation at reduced temperatures, BSCF cathodes may result in widespread practical implementation of SOFCs.